Identification and Analysis of Long Non-Coding RNAs Related to UV-B-Induced Anthocyanin Biosynthesis During Blood-Fleshed Peach (Prunus persica) Ripening - Zhang, Man; Zhang, Xiuqi; Wang, Haijing; Ye, Mao; Liu, Yating; Song, Zhihua; Du, Tingting; Cao, Hongyan; Song, Liqin; Xiao, Xiao; Liu, Jianzhen; Zhang, Libin; et al. (Frontiers in Genetics, 2022)
Blood flesh is a key fruit trait in peaches (Prunus persica) and can be attributed to the accumulation of anthocyanins. The roles of long non-coding RNAs (lncRNAs) have been highlighted by multiple studies in regulating fruit ripening, anthocyanin accumulation, and abiotic stress responses in many flowering plants. Such regulatory functions of lncRNAs in Prunus persica, nonetheless, have not been reported. In this research, we sequenced and analyzed the complete transcriptome of C3-20 (a blood-fleshed peach) fruit at four developmental stages. Analyses of the correlated genes and differentially expressed lncRNA target genes helped to forecast lncRNAs’ possible functions. The RNA-seq data were generated using high-throughput sequencing. In total, 17,456 putative lncRNAs, including 4,800 intergenic lncRNAs, 2,199 antisense lncRNAs, and 10,439 intronic lncRNAs were discovered, of which 4,871 differentially expressed lncRNAs (DE-lncRNAs) were annotated in the fruit developmental processes. The target genes of these DE-lncRNAs and their regulatory relationship identifying 21,795 cis-regulated and 18,271 trans-regulated targets of the DE-lncRNAs were in a similar way predicted by us. The enriched GO terms for the target genes included anthocyanin biosynthesis. Flavonoid biosynthesis and plant hormone signal transduction were also included in the enriched KEGG pathways. Co-expression network construction demonstrated that the highly expressed genes might co-regulate multiple other genes associated with auxin signal transduction and take effect in equal pathways. We discovered that lncRNAs, including LNC_000987, LNC_000693, LNC_001323, LNC_003610, LNC_001263, and LNC_003380, correlated with fruit that ripened and could take part in ethylene biosynthesis and metabolism and the ABA signaling pathway. Several essential transcription factors, such as ERFs, WRKY70, NAC56, and NAC72, may in a similar way regulate fruit ripening. Three DE-lncRNAs, XLOC_011933, XLOC_001865, and XLOC_042291, are involved in UV-B-induced anthocyanin biosynthesis and positively regulating UVR8 and COP10, were identified and characterized. Our discovery and characterization of XLOC_011933, XLOC_001865, and XLOC_042291 provide a more precise understanding and preliminarily establishes a theoretical framework for UV-B-induced flesh anthocyanin biosynthesis. This phenomenon might encourage more in-depth investigations to study the molecular mechanisms underlying peach flesh coloring.